2023
DOI: 10.1111/jcpe.13769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of periodontitis in dentate people between 2011 and 2020: A systematic review and meta‐analysis of epidemiological studies

Abstract: Aim The aim of the study was to evaluate the prevalence of periodontitis in dentate people between 2011 and 2020. Materials and Methods PUBMED, Web of Science, and LILACS were searched up to and including December 2021. Epidemiological studies reporting the prevalence of periodontitis conducted between 2011 and 2020 were eligible for inclusion in this review. Studies were grouped according to the case definition of confidence as confident (Centers for Disease Control [CDC] AAP 2012; CDC/AAP 2007; and Armitage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 91 publications
2
45
1
5
Order By: Relevance
“…Periodontitis, a chronic inflammatory disease affecting the tissue around teeth, can lead to alveolar bone destruction and eventual tooth loss if untreated 1 . A recent systematic review found that the global prevalence of periodontitis has increased to approximately 60% in the last decade (2011–2020), surpassing previous estimates from 1990 to 2010 2 . Its adverse effects extend beyond the oral cavity, influencing the onset and progression of systemic diseases such as cardiovascular disease, respiratory infections, and diabetes 3,4 .…”
Section: Introductionmentioning
confidence: 87%
“…Periodontitis, a chronic inflammatory disease affecting the tissue around teeth, can lead to alveolar bone destruction and eventual tooth loss if untreated 1 . A recent systematic review found that the global prevalence of periodontitis has increased to approximately 60% in the last decade (2011–2020), surpassing previous estimates from 1990 to 2010 2 . Its adverse effects extend beyond the oral cavity, influencing the onset and progression of systemic diseases such as cardiovascular disease, respiratory infections, and diabetes 3,4 .…”
Section: Introductionmentioning
confidence: 87%
“…1 Periodontitis is considered the sixth most common osteolytic disease affecting humans, 2 has a prevalence of 62.3%, and in its most severe form, can affect up to 23.6% of the world population. 3 The most current classification proposed by the global workshop is based on the complexity/severity and progression of the disease represented by Stages I-IV and Grades A-C. 4 Affected individuals clinically present bleeding on probing (BOP), suppuration, dental mobility, changes in the levels of insertion (clinical attachment loss [CAL]), and bone loss, ultimately leading to extraction or loss of teeth, which has a significant impact on the individual's oral health-related quality of life. 5 Therefore, its diagnosis is by clinical and radiographic examination.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a chronic and multifactorial inflammatory disease caused by constant exposure to a polymicrobial dysbiotic film with a high prevalence of Gram‐negative bacteria such as Prevotella intermedia , Fusobacterium nucleatum , Aggregatibacter actinomycetemcomitans , Porphyromonas gingivalis , Tannerella forsythia , and Treponema denticola , and in the presence of a dysregulated immune response in a genetically susceptible host 1 . Periodontitis is considered the sixth most common osteolytic disease affecting humans, 2 has a prevalence of 62.3%, and in its most severe form, can affect up to 23.6% of the world population 3 . The most current classification proposed by the global workshop is based on the complexity/severity and progression of the disease represented by Stages I–IV and Grades A–C 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a chronic inflammatory disease associated with dysbiotic subgingival biofilms. It is highly prevalent, affecting about 60% of adults worldwide (Trindade et al, 2023). Cross‐sectional and case–control studies have indicated that periodontitis is associated with an increased likelihood of hypertension (Munoz Aguilera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%